658. Effect of HIV Status on Tuberculosis Load as Detected by Xpert MTB/RIF in Sputum vs. Saliva Samples. (31st December 2020) - Burger, Zoe C; Aung, Si Thu; Aung, Hlaing Thazin; Rodwell, Timothy; Seifert, Marva
Abstract: Background: Tuberculosis (TB) is the most common co-infection among people living with HIV, but HIV positivity is associated with a lower Mycobacterium tuberculosis (MTB) bacillary load in sputum, making TB often difficult to diagnose with current diagnostic solutions. GeneXpert MTB/RIF (Cepheid, USA), a rapid, molecular diagnostic assay, has transformed the TB diagnostic landscape and can be used to diagnose TB and limited drug resistance in HIV patients from direct clinical samples in < 2 hours, but results can be significantly affected by sample bacterial load, which is quantified by the GeneXpert MTB/RIF (Xpert) instrument using Ct values. Our primary objective was to assess how a patient's HIV status affected their MTB bacterial load in sputum vs. saliva samples submitted for Xpert diagnosis of TB. Methods: We completed a retrospective analysis of >4, 000 patient records from the Myanmar National TB Program captured as part of a nation-wide electronic reporting system developed with the assistance of FIND (Geneva). De-identified records included HIV status, Xpert testing results, and for a subset of patients, specimen type. With this diagnostic information, we compared the distribution of MTB load (quantified by Xpert Ct values) in sputum and saliva in HIV positive vs. HIV negative patients using STATA. Results: Based on mean Ct value comparison independent of HIV status, saliva samples (mean Ct = 22.7) contained a significantly lower bacterial load of MTB as compared to sputum samples (mean Ct=19.2, p < .001).Within saliva samples, a lower bacterial load was also detected in HIV positive patients (mean Ct = 26.9) compared to HIV negative patients (mean Ct = 22.3, p< .05). Similarly, in sputum samples, a lower bacterial load was detected in HIV positive patients (mean Ct = 21.6) compared to HIV negative patients (mean Ct = 19.0, p < .001) (Figure 1). Figure 1. Ct Values by HIV Status and Specimen Type Conclusion: Sputum samples have a significantly higher bacterial load on average compared to saliva samples independent of HIV status. Additionally, when looking at both saliva and sputum as sample types, HIV positive patients have significantly lower bacterial load than individuals who are HIV negative. Based on these results, sputum is the optimal sample type for Xpert TB detection, especially in people living with HIV. Disclosures: All Authors : No reported disclosures